SPIRITUALITAS DAN GENDER: Sufi-Sufi Perempuan - M. Iqbal Maulana (Living Islam: Journal of Islamic Discourses, 2018)
Today there have been many studies of Sufism, but not many studies have discussed the involvement and contribution of women in the realm of Islamic mysticism in particular. This fact cannot be used as an excuse to say that Sufism, especially Islam, completely ignores the position and contribution of women. The few studies, once again, cannot be used as an excuse that women have little contribution and position in the development and spread of Sufism's teachings, doctrines and prac- tices.This paper discusses the equality of women and men not only in the conceptual level as stated in the Qur'an and Hadith. Furthermore, a number of female Sufi fig- ures such as Rabi'ah Adawiyah, Aishah al-Ba'uniyyah, Jahan Malek Khatun, Mahsati Ganjavi (Persia), Habba Khatoon, Jahanara Begum (India), were shown, which proved that women had equal opportunities in achieving spiritual knowledge.